2015
DOI: 10.1021/acs.langmuir.5b02633
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and Specificity of Nanoscale Adhesion Forces Measured between Self-Assembled Monolayers and Lignocellulosic Substrates: A Chemical Force Microscopy Study

Abstract: Lack of fundamental understanding of cellulase interactions with different plant cell wall components during cellulose saccharification hinders progress toward achieving an economic production of biofuels from renewable plant biomass. Here, chemical force microscopy (CFM) was utilized to quantify the interactions between two surfaces that model either hydrophilic or hydrophobic functional groups of cellulases and a set of lignocellulosic substrates prepared through Kraft, sulfite, or organosolv pulping with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(45 citation statements)
references
References 59 publications
5
40
0
Order By: Relevance
“…The fibers of lignocellulosic substrates were attached to silicon wafers for AFM experiments via a protocol described previously. 12 Briefly, piranha solution (4:1 H 2 SO 4 /H 2 O 2 )-cleaned silicon wafers were coated with 0.01% poly-L-lysine (PLL), and a 50 μL aliquot of a 1 mg/ mL water suspension of the fiber of interest was added to the PLLcoated silicon wafer for substrate attachment. The water in the suspension droplet was then allowed to evaporate overnight in a vacuumed desiccator.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fibers of lignocellulosic substrates were attached to silicon wafers for AFM experiments via a protocol described previously. 12 Briefly, piranha solution (4:1 H 2 SO 4 /H 2 O 2 )-cleaned silicon wafers were coated with 0.01% poly-L-lysine (PLL), and a 50 μL aliquot of a 1 mg/ mL water suspension of the fiber of interest was added to the PLLcoated silicon wafer for substrate attachment. The water in the suspension droplet was then allowed to evaporate overnight in a vacuumed desiccator.…”
Section: Methodsmentioning
confidence: 99%
“…The cantilever modification with methyl functional groups was performed as described previously. 12 Briefly, gold-coated AFM cantilevers were immersed in a 1 mM ethanolic solution of 1-octadecanethiol for 2 h. The cantilevers were then washed with 190 proof ethanol and dried in a stream of nitrogen before force measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured forces are then mapped and compared to the surface structures detected by the topological imaging for further analysis. These measurements are proven to be helpful in identification purposes, to determine compatibility between two materials, and to predict interactions between materials [219]. CFM has proven its use in the analysis of biomaterial and biopolymer fields, and has been used in the characterization of cellulose [220], chitosan [82], and DNA [221].…”
Section: (B) Chemical Force Microscopymentioning
confidence: 99%
“…It was reported that biodegradation rapidly decreases xylem toughness measured by dynamic tests (Clausen 2010). Adhesive forces and interactions between neighbouring cells are essential for both cell development and tissue morphogenesis (Lommel et al 2013;Arslan et al 2015). In addition, changes in adhesion may be a good indicator of alterations in cell wall biopolymer distribution and orientation as well as chemical alterations in cell walls (Ďurkovič et al 2013).…”
Section: Introductionmentioning
confidence: 99%